Cover Image, Volume 56, Issue 21. Issue 21 (1st November 2018) - Unknown
Abstract : The molecule DiEthylHexyl Phthalate used as a plasticizer in PVC looks like a frog when drawn out in ChemDraw. The phthalate molecules in PVC leach out over time and escape into the environment. Chad M. Higa, Andy T. Tek, Rudy J. Wojtecki, and Rebecca Braslau describe new phthalate mimics with one tail (tadpoles) in their work described on page 2397. This new phthalate mimic is covalently linked to the PVC; themolecules cannot leach out into the environment, but still act as effective plasticizers. (DOI:10.1002/pola29205 )